Acid-base dissociation constants of o-phthalic acid in acetonitrile/water mixtures over the (15 to 50) °C temperature range and related thermodynamic quantities - Gagliardi, Leonardo Gabriel (2010)
Potassium hydrogen phthalate (KHP) is a primary titrimetric standard, and KHP solutions are also used as standards for pH reference values, in pure water or in hydrorganic solvent mixtures. However, the pH of these solutions can be affected by any shift in the pKa1 or pKa2 of the substance due to changes in the solvent composition or temperature. In this work, the two dissociation constants of o-phthalic acid were independently determined for different compositions of acetonitrile/water mixtures within the range from 0 % to 70 % by weight, in steps of 10 %, and at different temperatures from (15 to 50) °C, in steps of 5 °C. The dependence of ln Ka on the inverse of temperature has been examined by using statistical methods, and the corresponding ionization thermodynamic functions have been calculated for different acetonitrile compositions.